IMPACT OF PATIENTS' COMPLIANCE TO TREATMENT COURSE UPON TUBERCULOSIS DISEASE COMPLICATIONS AT RESPIRATORY AND CHEST DISEASE OUT-PATIENTS CLINIC IN AMARA CITY - Saad Sabri Shamkh; Zahid Jasim Mohammed (Scholar Express Journals, 2022)
tuberculosis is a communicable disease that is spread through the air, caused by bacteria called (mycobacterium tuberculosis). Mostly affect the lung but also affect any part of the body
Keywords: Tuberculosis Complications; Patients’ Compliance; Treatment Course